Case report: A vertebral bone spur as an etiology for spinal cord herniation: case presentation, surgical technique, and review of the literature - Hunziker, S.; Örgel, A.; Tatagiba, M.; Adib, S. D. (Frontiers in Surgery, 2023)
Objective: The pathophysiology of idiopathic spinal cord herniation (ISCH) remains unknown. However, several different factors have been postulated, such as congenital causes (ventral dura mater duplication, preexisting pseudomeningocele, or other congenital dural defects), inflammation, remote spinal trauma, or thoracic disc herniation. Herein, diagnosis and surgical treatment of a spinal cord herniation case caused by an intraspinal bone spur were presented along with a relevant literature review. Case presentation: A 56-year-old male patient presented with a non-traumatic Brown–Sequard syndrome persisting for over 1 year. A magnetic resonance imaging of the spinal axis revealed a ventral spinal cord displacement in the level of T 6/7. A supplementary thin-sliced computed tomography of the spine revealed a bone spur at the same level. For neurosurgical intervention T 6 and T 7 laminectomy was performed. The cranial and caudal end of the right paramedian ventral dural defect was visualized and enlarged. Following the extradural spinal cord mobilization by denticulate ligament transection, the spinal cord was finally released. The spinal cord was rotated and the ventral closure of the dural defect was performed by continuous suture. The patient recovered from surgery without additional deficits. The patients’ postoperative gait, sensory, and motor function deficits improved, and further neurological deterioration was prevented. Conclusion: Since the first description of spinal cord herniation by Wortzman et al. in 1974, approximately 260 cases have been reported in the literature. In addition to other causes, intraspinal bone spur may be a cause of spinal cord herniation.